IMPLEMENTATION OF GUIDED DISCOVERY LEARNING MODEL USING PHET SIMULATIONS ON IDEAL GAS MATERIALS IN XI MIPA OF STATE SENIOR HIGH SCHOOL 2 NGANJUK - SABRINA, FITRIATUS; , WASIS (Inovasi Pendidikan Fisika, 2019)
This research aims to analyze the implementation of guided discovery learning model using PhET simulations. More specifically, it aims to analyze a lesson about ideal gas. It is pre experimental research with one grup pretest-posttest design. Using random sampling, students of XI MIPA 4, XI MIPA 5, and XI MIPA 7 were involved. Methods of data collection were observation. The data analysis techiques were analysis of implementation of learning. The data analysis reveals that the implementation of guided discovery using PhET simulations shows that PhET simulations in class XI MIPA 4, XI MIPA 5, and XI MIPA 7 in State Senior High School 2 Nganjuk was successfully carried out. Key Words: Guided discovery, PhET, ideal gas, implementation of learning